Leadership Style, Organizational Culture, and Job Stress toward Organizational Commitment: Gaya Kepemimpinan, Budaya Organisasi, dan Stres Kerja terhadap Komitmen Organisasi - Susilo; Panji , Agil; Lilik (Indonesian Journal of Law and Economics Review, 2025)
Background: Human resources play a key role in achieving organizational success, and maintaining employee commitment is essential for long-term performance. Specific Background: PT. Ciomas Adisatwa Sidoarjo has faced issues of low employee discipline and stress, which may be influenced by leadership style and organizational culture. Gap: Few studies have explored these relationships simultaneously in the context of poultry processing companies in Indonesia. Aims: This study aims to examine the relationship between leadership style, organizational culture, and job stress toward organizational commitment. Results: The findings show that leadership style and organizational culture have significant positive effects, while job stress has a significant negative effect on organizational commitment. Novelty: The study highlights the simultaneous influence of behavioral and psychological factors in the workplace. Implications: The results suggest that improving leadership practices and organizational culture can enhance employee loyalty and reduce turnover. Highlights:• Leadership and culture increase employee commitment.• Job stress decreases organizational loyalty.• Simultaneous influence of leadership, culture, and stress. Keywords: Leadership, Organizational Culture, Job Stress, Commitment, Employee Performance